An orchid astronomy - Hayden, Tasnuva (Brave & brilliant series, 2022)
"A five-pointed, language-infused star map cataloging a migrating requiem of memories, mythologies, and science in the face of climate catastrophe and personal collapse. Sophie grew up in Veslefjord, deep in the Norwegian North, where the ice stretches to the horizon and the long Arctic night is filled with stories about the animals of the sea, ice, and sky. Now the ice is melting and the animals are dying. Sophie's mother is also dead, leaving behind a daughter and a lover on the melting permafrost. An Orchid Astronomy is the story of Sophie, of her personal trauma and of climate catastrophe, told in striking experimental poetry. Crossing poetic styles and genres, words and sentences flow and break, twist into images, and cluster together like the Arctic stars. Coming together in a sustained narrative, these poems ask how we grapple with magnificent loss, searching for solutions in science, in mythology, in storytelling and ultimately, in our relived memories. Challenging, powerful, and beautiful, An Orchid Astronomy wrestles with the grief we feel for the loss of those we love and grief for the changing world. In the language of mass extinction and the unknowable sky, Tasnuva Hayden fearlessly explores the nuances of personal collapse, sublimated desire, unfulfilled longing, and the ways we must move forward in the face of the impossible in poetry that dazzles like the moon on a midwinter night."--